Changes of primary and secondary metabolites in barley plants exposed to CdO nanoparticles - Večeřová, Kristýna; Večeřa, Zbyněk; Dočekal, Bohumil; Oravec, Michal; Pompeiano, Antonio; Tříska, Jan; Urban, Otmar (Environmental pollution (1987), 2016)
The environmental fate of airborne nanoparticles and their toxicity to plants is not yet fully understood. Pot-grown barley plants with second leaves developed were therefore exposed to CdO nanoparticles (CdONPs) of ecologically relevant size (7-60 nm) and concentration (2.03 ± 0.45 × 10(5) particles cm(-3)) in air for 3 weeks. An experiment was designed to test the effects of different treatments when only leaves (T1); leaves and soil substrate (T2); and leaves, soil, and water supply were exposed to nanoparticles (T3). A fourth, control group of plants was left without treatment (T0). Although CdONPs were directly absorbed by leaves from the air, a part of leaf-allocated Cd was also transported from roots by transpiration flow. Chromatographic assays revealed that CdONPs had a significant effect on total content of primary metabolites (amino acids and saccharides) but no significant effect on total content of secondary metabolites (phenolic compounds, Krebs cycle acids, and fatty acids). In addition, the compositions of individual metabolite classes were affected by CdONP treatment. For example, tryptophan and phenylalanine were the most affected amino acids in both analysed organs, while ferulic acid and isovitexin constituted the polyphenols most affected in leaves. Even though CdONP treatment had no effect on total fatty acids content, there were significant changes in the composition of saturated and unsaturated fatty acids in both the roots and leaves of treated plants. Although the results indicate the most pronounced effect in T3 plants as compared to T1 and T2 plants, even just leaf exposure to CdONPs has the potential to induce changes in plant metabolism.
Keywords: ječmen (rod); oxidy; sekundární metabolismus; listy rostlin; Soil Pollutants; Oxides; fenoly; apigenin; Nanoparticles; Phenols; látky znečišťující půdu; Water Pollutants; Apigenin; Cadmium Compounds; Plant Leaves; Coumaric Acids; nanočástice; Plant Roots; Secondary Metabolism; látky znečišťující vodu; Hordeum; kyseliny kumarové; Amino Acids; aminokyseliny; sloučeniny kadmia; kořeny rostlin